A heuristic analysis of equity and equality in the institutionalisation of property rights: the Baliraja water distribution experiment, India. (9th February 2009) - Sivramkrishna, Sashi; Jyotishi, Amalendu
Natural resource management perceived as a search for institutions that can ensure simultaneous fulfilment of three goals: productivity (or efficiency), sustainability and equity. In this article, we study the implications of pursuing the goal of equity in the management of surface water resources for irrigation with a heuristic model incorporating a Leontief-type fixed production function. The analysis has been carried out in the backdrop of the Baliraja water distribution experiment in India. One suggestion is that the allocating tradable water rights over water, a common property natural resource, can be used as an instrument to improve equity. Unfortunately, advocating the use of water distribution as an instrument of poverty alleviation is fraught with implicit assumptions about the rural economy and uncertain outcomes. It is important for planners to understand that the concepts of equity and equality are applicable to inputs and outputs or outcomes. We attempt to understand the implications of equality in water distribution on social welfare with a simple heuristic analysis. Theoretical analysis shows the possible outcomes of such a policy and also intended to raise pertinent questions and hypotheses in studying the effectiveness of irrigation and watershed initiatives where rights over water have been redistributed equally.